Determining the viability of Schistosoma mansoni cercariae using fluorescence assays: An application for water treatment. - Laura Braun; Lucinda Hazell; Alexander J Webb; Fiona Allan; Aidan M Emery; Michael R Templeton (Public Library of Science (PLoS), 2020)
Background Schistosome cercariae are the human-infectious stage of the Schistosoma parasite. They are shed by snail intermediate hosts living in freshwater, and penetrate the skin of the human host to develop into schistosomes, resulting in schistosomiasis infection. Water treatment (e.g. filtration or chlorination) is one way of cutting disease transmission; it kills or removes cercariae to provide safe water for people to use for activities such as bathing or laundry as an alternative to infested lakes or rivers. At present, there is no standard method for assessing the effectiveness of water treatment processes on cercariae. Examining cercarial movement under a microscope is the most common method, yet it is subjective and time-consuming. Hence, there is a need to develop and verify accurate, high-throughput assays for quantifying cercarial viability. Method We tested two fluorescence assays for their ability to accurately determine cercarial viability in water samples, using S. mansoni cercariae released from infected snails in the Schistosomiasis Collection at the Natural History Museum, London. These assays consist of dual stains, namely a vital and non-vital dye; fluorescein diacetate (FDA) and Hoechst, and FDA and Propidium Iodide. We also compared the results of the fluorescence assays to the viability determined by microscopy. Conclusion Both fluorescence assays can detect the viability of cercariae to an accuracy of at least 92.2% ± 6.3%. Comparing the assays to microscopy, no statistically significant difference was found between the method's viability results. However, the fluorescence assays are less subjective and less time-consuming than microscopy, and therefore present a promising method for quantifying the viability of schistosome cercariae in water samples.